The effects of inhaled formaldehyde on the activities of some metabolic enzymes in the liver of male rats: Subchronic (13-weeks) effects - Ramazan Yilmaz, H.; Aslan Özen, O.; Özyurt, Hüseyin; Songur, Ahmet; Şahin, Şemsettin; Sarsilmaz, Mustafa (My University, 2004)
We aimed to investigate the effects of different formaldehyde (FA) concentrations on some enzyme activities that take part in metabolic pathways in the liver. The enzymes studied were hexokinase (HK), glucose-6-phosphate dehydrogenase (G6PD), 6-phosphogluconate dehydrogenase (6PGD), lactate dehydrogenase (LDH), and malate dehydrogenase (MDH) which are included in the three main metabolic pathways; glycolysis, citric acid cycle, and pentose phosphate pathway. Thirty male Wistar albino rats were raudemly divided into 3 separate groups (10 per group). The first ten rats were used as control (grup I). Rats were exposed to atmosphere containing 10 and 20 ppm FA continuously (8 hours per day, 5 days per week) in groups II and III. HK, G6PD, 6PGD, LDH, and MDH activities were measured in liver tissues. The results showed a remarkable reduction in G6PD and 6PGD activities, significant increase in MDH activity in liver tissues from rats exposed to 10 ppm FA for 13-weeks. There were no differences in the activities of HK and LDH between test and control groups. Conversely G6PD activity was decreased and MDH activity was increased in liver tissues from rats exposed to 20 ppm FA for 13-weeks. These results may suggest the possible changing effect of FA inhalation on metabolic enzymes in liver.
Keywords: 6-phosphogluconate dehydrogenase; Formaldehyde; Glucose-6-phosphate dehydrogenase; Hexokinase; Lactate dehydrogenase; Liver; Malate dehydrogenase